Handbook of otolaryngic allergy - Franzese, Christine B. (Thieme, 2019)
The quintessential how-to guide on treating allergies for day-to-day practice While encyclopedic tomes on the treatment of allergies have a place on the library shelves of otolaryngologists, Handbook of Otolaryngic Allergy provides a user-friendly office resource clinicians can consult on a daily basis. Written by Christine Franzese, Cecelia Damask, Sarah Wise, and Matthew Ryan, the book encompasses the basic science of allergies, essential knowledge, and how to perform each procedure. Part one starts with basic immunology and allergic rhinitis definition and classifications, followed by discussion.